DIGITALISASI KONVERSI PENILAIAN ANGKA KREDIT (PAK) PEGAWAI MENGGUNAKAN METODE AGILE DEVELOPMENT DI POLITEKNIK NEGERI SRIWIJAYA - Sartika, Citra Dewi; Nagara, Bangga Surya; Mirad, Ahmad; Da'iyan, Iqbal Nur; Erlangga, Yusta; Syakira, Nadhira (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2025)
This study aims to design a web-based digital system to support the conversion process of Credit Score Assessment (PAK) in a more efficient, accurate, and transparent manner. PAK is an essential instrument for the career development of lecturers and educational staff. At Politeknik Negeri Sriwijaya, the conversion process is still conducted manually, which often leads to delays and potential data errors. The research employs the Agile Development method, a software development approach that is iterative and flexible. The stages of the study include requirements analysis, system and database design, and website development. The results show that the developed system can perform automatic calculations, manage data in a structured manner, and provide a user-friendly interface. With the implementation of this system, the PAK conversion process becomes faster, more accurate, and contributes to improving the quality of administrative services at Politeknik Negeri Sriwijaya.